2021
DOI: 10.1098/rstb.2020.0299
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reputation on inequality in network cooperation games

Abstract: In the last several decades, ample evidence from across evolutionary biology, behavioural economics and econophysics has solidified our knowledge that reputation can promote cooperation across different contexts and environments. Higher levels of cooperation entail higher final payoffs on average, but how are these payoffs distributed among individuals? This study investigates how public and objective reputational information affects payoff inequality in repeated social dilemma interactions in large groups. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Both cooperation 1 5 and resource inequality 6 , 7 are universal but variable across human societies. Although several studies have suggested that variation in material wealth inequality and cooperation may be linked 2 , 8 10 , we currently know little about how inequality in material wealth or endowments impacts cooperation 8 or how cooperation, in turn, influences inequalities 11 . We study the bidirectional effects of cooperation and inequality in dynamic networks, where ties between alters represent opportunities to cooperate 8 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Both cooperation 1 5 and resource inequality 6 , 7 are universal but variable across human societies. Although several studies have suggested that variation in material wealth inequality and cooperation may be linked 2 , 8 10 , we currently know little about how inequality in material wealth or endowments impacts cooperation 8 or how cooperation, in turn, influences inequalities 11 . We study the bidirectional effects of cooperation and inequality in dynamic networks, where ties between alters represent opportunities to cooperate 8 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For cooperation to persist, cooperators, on average, must be better-off than non-cooperators. Tsvetkova [122] investigates how public and objective reputational information affects payoff inequality in repeated social dilemma interactions in large groups with the use of an agent-based model with simple decision heuristics and varying partner matching rules. She demonstrates that reputational information does not necessarily increase inequality in strategically updated networks, and actually decreases it in randomly rewired networks.…”
Section: This Issue's Contributionsmentioning
confidence: 99%
“…Our focus has been less on the stable set of strategies that may be employed, and more on their consequences (cf. [12,63,84]). We hope that this emphasis on the structural outcomes of individuals' strategic decisions will prompt more exploration in the evolutionary sciences.…”
Section: Conclusion: Future Directionsmentioning
confidence: 99%